The Role of Bpjs Officers in Cengkareng Hospital (A Study Based On Bpjs Law Perspective) - Arianto, Henry; Subandi Alda, Lili; Olivia, Fitria; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
This thesis discusses the role of BPJS Health officers in Cengkareng Regional Hospital based on the BPJS law. The problem is obtained in this thesis is the role of BPJS officers in order to fulfill the rights and obligations of patients in Cengkareng hospital and how sanctions for bpjs officers are not performing duties at Cengkareng hospital. This type of research is empirical and the whole is done using qualitative methods. This research shows that there is a BPJS who has committed violations in the Implementation of its Role in Cengkareng District Hospital. The results of the study suggest that there needs to be an evaluation of BPJS officers in their roles so that in implementing their roles in the daytime there will be no longer violations that harm patients in the hospital and if there are still BPJS officers who have not played their roles well then strict sanctions from the government will be given. complaints from the hospital or patient. Patients in this case must act decisively and dare to take decisions to the hospital so that the hospital immediately responds quickly to complain about violations committed by BPJS officers.